Gut Microbiota‐Associated Metabolites Affected the Susceptibility to Heart Health Abnormality in Young Migrants at High‐Altitude - Yongqiang Zhou; Zhexin Ni; Jingjing Liu; Dezhi Sun; Pan Shen; Xi Chen; Gaofu Li; Zhijie Bai; Yangyi Hu; Ningning Wang; Rui Wang; Lina Guan; et al. (Exploration)
ABSTRACT Young migrants, particularly those at high altitudes, are predisposed to heart health abnormalities, including high‐altitude heart disease. Despite the profound impact of hypobaric hypoxia on the gut microbial community, the understanding of the roles played by gut microbiota and gut microbiota‐associated serum metabolites in high‐altitude heart diseases remains limited. Therefore, we conducted a comprehensive multi‐omics analysis involving 230 graduates from the same university, with 163 Tibetan Plateau migrants and 67 Chengdu Plain residents, and identified 206 differential metabolites (82 in serum and 124 in feces) and 369 species that differed between migrants and residents. Among these, 27 microbial species and four metabolites (Ketoglutaric acid, L‐Aspartic acid, 3‐Guanidinopropionic acid, betaine) detected in both serum and feces were found to be associated with migrants exhibiting compromised heart health, as diagnosed through clinical examinations. Notably, the abundances of Veillonella rogosae and Streptococcus rubneri were correlated with serum levels of L‐Aspartic acid, betaine, and Ketoglutaric acid in heart health‐abnormal individuals. Validation of these microbiome biomarkers and gut microbiota‐associated serum metabolites in an independent cohort demonstrated their excellent predictive ability for indicating heart health abnormalities in migrants (AUC = 0.7857). Furthermore, supplementation with these identified species or gut microbiota‐associated serum metabolites effectively mitigated hypobaric hypoxia‐induced increases in serum lactate, glycolysis, myocardial damage, and cardiac hypertrophy. Integrated analysis revealed that the alterations in the gut microbiome negatively regulated key metabolic pathways such as the malate‐aspartate shuttle, tricarboxylic acid cycle, and oxidative phosphorylation in heart health‐abnormal individuals. The migration to high‐altitude plateaus significantly reshaped the gut microbiome and metabolome signatures. Lower abundances of Veillonella rogosae, Streptococcus rubneri, and gut microbiota‐associated serum metabolites promoted the remodeling of metabolic processes, thereby increasing susceptibility to high‐altitude heart health abnormalities. Overall, our findings elucidate the microbial mechanisms underlying high‐altitude heart disease and provide valuable insights for potential early intervention strategies in this context.